A poly(dimethylsiloxane)-based solid-phase microchip platform for dual detection of Pseudorabies virus gD and gE antibodies - Pan, Jiaojiao; Li, Yufang; Wang, Tongyan; Chang, Jingfeng; Hao, Liying; Chen, Junjie; Peng, Wuping; Deng, Junhua; Huang, Baicheng; Tian, Kegong (Frontiers in Cellular and Infection Microbiology, 2022)
Pseudorabies caused by pseudorabies virus (PRV) infection is still a major disease affecting the pig industry, its eradication depends on effective vaccination and antibody (Ab) detection. For a more rapid and accurate PRV detection method that is suitable for clinical application, here, we established a poly(dimethylsiloxane)-based (efficient removal of nonspecific binding) solid-phase protein chip platform (blocking ELISA) for dual detection of PRV gD and gE Abs. The purified gD and gE proteins expressed in baculovirus were coated into the highly hydrophobic nanomembrane by an automatic spotter, and the gray values measured by scanner were used for the S/N (sample/negative) value calculation (gD and gE Abs standard, positive: S/N value ≤ 0.6; negative: S/N value> 0.7; suspicious: 0.6 < S/N≤0.7). The method showed an equal sensitivity in the gD Ab test of immunized pig serum samples compared to the neutralization test, and higher sensitivity in the gE Ab test compared to the commercial gE Ab detection kit. In the clinical evaluation, we found an agreement of 100% (122/122) in the gD Ab detection compared to the neutralization test, and an agreement of 97.5% (119/122) in the gE Ab detection compared to the commercial PRV gE Ab detection kit. In summary, the protein chip platform for dual detection of PRV gD and gE Abs showed high sensitivity and specificity, which is suitable for PRV immune efficacy evaluation and epidemic monitoring.